Constitutional Identity Between Riga and Strasbourg: The Courts’ Dialogue Developing Latvian Constitutional Law - Artūrs Kučs; Jānis Pleps (Law: Journal of the University of Latvia)
The article provides insight into the recent development of the concept of constitutional identity in the Latvian legal system. The authors mainly focus on the dialogue between the national highest courts, especially the Constitutional Court, and the European Court of Human Rights and the Court of Justice of the European Union, concerning the concept of constitutional identity.